Trehalose Protects against Superoxide Dismutase 1 Proteinopathy in an Amyotrophic Lateral Sclerosis Model - Rayne S. S. Magalhães; José R. Monteiro Neto; Gabriela D. Ribeiro; Luan H. Paranhos; Elis C. A. Eleutherio (MDPI AG, 2024)
This work aimed to study the effect of trehalose in protecting cells against Sod1 proteinopathy associated with amyotrophic lateral sclerosis (ALS). Humanized yeast cells in which native Sod1 was replaced by wild-type human Sod1 or an ALS mutant (WT-A4V Sod1 heterodimer) were used as the experimental model. Cells were treated with 10% trehalose (p/v) before or after the appearance of hSod1 proteinopathy induced by oxidative stress. In both conditions, trehalose reduced the number of cells with Sod1 inclusions, increased Sod1 activity, and decreased the levels of intracellular oxidation, demonstrating that trehalose avoids Sod1 misfolding and loss of function in response to oxidative stress. The survival rates of ALS Sod1 cells stressed in the presence of trehalose were 60% higher than in their absence. Treatment with trehalose after the appearance of Sod1 inclusions in cells expressing WT Sod1 doubled longevity; after 5 days, non-treated cells did not survive, but 15% of cells treated with sugar were still alive. Altogether, our results emphasize the potential of trehalose as a novel therapy, which might be applied preventively in ALS patients with a family history of the disease or after diagnosis in ALS patients who discover the disease following the first symptoms.